Magnetic Particle Imaging of Macrophages Associated with Cancer: Filling the Voids Left by Iron-Based Magnetic Resonance Imaging. - Makela, Ashley V.; Gaudet, Jeffrey M.; Schott, Melissa A.; Sehl, Olivia C.; Contag, Christopher H.; Foster, Paula J. (Molecular Imaging & Biology, 2020)
Purpose: Magnetic particle imaging (MPI) is an emerging molecular imaging technique that directly detects iron nanoparticles distributed in living subjects. Compared with imaging iron with magnetic resonance imaging (MRI), MPI signal can be measured to determine iron content in specific regions. In this paper, the detection of iron-labeled macrophages associated with cancer by MRI and MPI was compared.Procedures: Imaging was performed on 4T1 tumor-bearing mice 16-21 days post-cancer cell implantation, 24 h after intravenous injection of Ferucarbotran, a superparamagnetic iron oxide (SPIO) or Ferumoxytol, an ultra-small SPIO. Images of living mice were acquired on a 3T clinical MRI (General Electric, n = 6) or MPI (Magnetic Insight, n = 10) system. After imaging, tumors and lungs were removed, imaged by MPI and examined by histology.Results: MRI signal voids were observed within all tumors. In vivo, MPI signals were observed in the tumors of 4 of 5 mice after the administration of each contrast agent and in all excised tumors. Signal voids visualized by MRI were more apparent in tumors of mice injected with Ferumoxytol than those that received Ferucarbotran; this was consistent with iron content measured by MPI. Signal voids relating to macrophage uptake of iron were not detected in lungs by MRI, since air also appears hypointense. In vivo, MPI could not differentiate between iron in the lungs vs the high signal from iron in the liver. However, once the lungs were excised, MPI signal was detectable and quantifiable. Histologic examination confirmed iron within macrophages present in the tumors.Conclusions: MPI provides quantitative information on in vivo iron labeling of macrophages that is not attainable with MRI. The optimal iron nanoparticle for MPI in general is still under investigation; however, for MPI imaging of macrophages labeled in vivo by intravenous administration, Ferumoxytol nanoparticles were superior to Ferucarbotran.